Anthocyanins in metabolites of purple corn - Cai, Taoyang; Ge-Zhang, Shangjie; Song, Mingbo (Frontiers in Plant Science, 2023)
Purple corn (Zea mays L.) is a special corn variety, rich in a large number of anthocyanins and other functional phytochemicals, and has always ranked high in the economic benefits of the corn industry. However, at present, the research on the stability of agronomic traits and the interaction between genotype and environment of cereal crops mostly focuses on yield, but the research on quality traits such as anthocyanin content and antioxidant activity is still very scarce. This review starts with expounding the biosynthesis process of anthocyanins and phenols in purple corn and the gene regulation mechanism behind it, and points out the environmental factors that affect its metabolism and stability, in order to promote corn production by improving the level of antioxidant compounds and provide new opportunities for corn breeders and growers.